Can Early Patient-reported Outcomes Be Used to Identify Patients at Risk for Poor 1-Year Health Outcomes After Lumbar Laminectomy With Arthrodesis?. Issue 15 (1st August 2018) - Purvis, Taylor E.; Neuman, Brian J.; Riley, Lee H.; Skolasky, Richard L.
Abstract : Study Design: Prospective cohort. Objective: Determine A) between-patient variability in patient-reported outcomes (PROs) at four postoperative time points; B) within-patient correlation of 1-year PROs with PROs at three earlier time points; and C) ability of early PROs to predict 1-year PROs after lumbar laminectomy with arthrodesis. Summary of Background Data: It is unclear whether early PROs can help identify patients at risk for poor health outcomes. Methods: Between 2015 and 2016, we assessed pre- and postoperative back pain, leg pain, disability, physical health, and mental health in 146 patients. We examined PRO variability between patients and correlations within patients during the first postoperative year. For early (⩽3-mo) and 1-year PROs, we examined concordance between experiencing a minimal important difference (MID) early and at 1 year and odds of experiencing a 1-year MID given early absence of a MID. Results: Postoperatively, we found increasing between-patient variability of PROs. For individual patients, we found moderate to strong between-assessment correlations (intraclass correlations) between repeated PROs (back pain, 0.47; leg pain, 0.51; disability, 0.47; physical health, 0.63; mental health, 0.53). Early MIDs were experienced for back pain (57%), leg pain (52%), physical health (38%), disability (34%), and mental health (16%). Concordance was moderate for leg pain (0.48), mental health (0.46), disability (0.38), back pain (0.36), and physical health (0.25). In patients without an early MID, odds of experiencing a MID at 1 year were low for physical health (odds ratio [OR] = 0.33), back pain (OR = 0.30), leg pain (OR = 0.14), and disability (OR = 0.11) but not mental health (OR = 0.50). Conclusion: Although postoperative recovery is variable, early PROs can identify patients at risk for poor 1-year outcomes and may help tailor care during the first year after lumbar laminectomy with arthrodesis. Level of Evidence: 2